2008
DOI: 10.1007/s12105-008-0078-x
|View full text |Cite
|
Sign up to set email alerts
|

Kimura Disease of the Epiglottis

Abstract: Kimura disease is a distinct clinicopathological entity of a benign chronic inflammatory disorder of unknown etiology. It is endemic in Oriental Asians, but sporadic and relatively rare in the West, both in whites and blacks alike. It usually presents as a mass lesion, most commonly in the head and neck region. It had for a long time been confused as synonymous with angiolymphoid hyperplasia with esinophilia. It can impose a challenging diagnosis both clinically and pathologically, especially in non-endemic ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Other sites such as the oral cavity, axilla, groin, limbs, and trunk have also been described, but the involvement of the respiratory tract is rare. To our knowledge, 10 cases of KD centered around the epiglottis have appeared in the English and Japanese literature [7][8][9][10][11][12][13][14][15][16]. Our case provides an additional example (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Other sites such as the oral cavity, axilla, groin, limbs, and trunk have also been described, but the involvement of the respiratory tract is rare. To our knowledge, 10 cases of KD centered around the epiglottis have appeared in the English and Japanese literature [7][8][9][10][11][12][13][14][15][16]. Our case provides an additional example (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Laryngeal lymphangiomas typically arise in the supraglottic larynx within the epiglottis, aryepiglottic folds, and arytenoid cartilages, and are hyperintense on T2-weighted MRI. 13,49 Despite the predominance in the pediatric population, Seven et al. (2004) reported a 37-year-old male who initially presented with acute epiglottitis.…”
Section: Discussionmentioning
confidence: 99%
“…While the presence of calcifications raised the possibility of a chondrosarcoma or tuberculosis, amyloidosis tends to be isointense on T1-weighted MRI and slightly hyperintense on T2-weighted MRI, while chondrosarcoma tends to be T1 hypo-or isointense and markedly T2 hyperintense. 44 Badr et al (2008) reported a case of Kimura disease, a benign chronic inflammatory disease that is likely immune driven, manifesting as a single polypoid epiglottic mass in a 37-year-old female who presented with difficulty breathing and swallowing. While usually presenting as a subcutaneous mass, the epiglottis may be involved.…”
mentioning
confidence: 99%
“…Adjuvant therapy in the form of steroids, cytotoxic therapy, and radiation therapy also have been used in some cases. 9 Kimura’s disease is associated with excellent prognosis; only few local and distal recurrences also have been reported. 10…”
Section: Discussionmentioning
confidence: 99%